Radio Television Malaysia (RTM) In Penang: A Study Of The Structure And Operations Of The Radio Station And Its News And Programmes Contents. - Pung, Kim Ying (Universiti Sains Malaysia, 1982)
This academic exercise is study of the structure and operations of RTM in Penang. It will also analyse the role the station plays in fulfilling the objectives of STM. The opening Chapter outlines the need for such a study in Malaysia in particular.